C’était bien à l’époque mais l’avenir iko sombre - Waldburger, Daniela (Brill, 2025)
How can exploitative living and working conditions be remembered with nostalgia? This monograph offers an analysis of the specific form of the 'nostalgia-based master narrative' used by ex-mineworkers in Lubumbashi (DR Congo) as a solution to current problems and the future. On the methodological level, questions of crucial importance for the above-mentioned point are addressed, such as contextual and group knowledge production and the communicative processes involved.